IPTEKS PENGENDALIAN INTERN DALAM PROSEDUR PENCAIRAN KREDIT KONSUMTIF PADA PT. BANK SULUTGO CABANG UTAMA - Maria, Brigita; Chandra, Vionalisa; Muliad, Halim Ellena; Elim, Inggriani (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2020)
In conducting credit distribution to the public, there are several procedures that must be carried out before credit can be disbursed. Lending also needs to pay attention to internal controls within the company. The purpose of this study is to evaluate whether internal control in credit disbursement procedures is in accordance with the theory of control according to COSO. This research method is a qualitative method. Data collection techniques are interviews and documentation. The results of this study indicate that the company has not fully implemented internal controls based on COSO, particularly environmental control and monitoring.